Formalization of support for decisions and recognition for the environment and the sector. Key factors for good governance. Perception in Colombian companies (2018)
During the development of their activities, companies modify some factors related to the decisions and actions to be taken in the general and specific environment. In this process, they implement norms and policies to optimize the use of resources, formulate regulations, respect the right as an administrative principle, create mechanisms of self-control, demand responsibilities from their collaborators and make decisions. Obviously, all are tactics to formalize business management and the decisions to be made, with a view to maintaining good governance and being recognized in the environment and the sector. The objective of the study is to analyze the perception of Colombian entrepreneurs in relation to the formalization of support for decisions and the recognition by the environment and the sector, the actions that for a good government. The sample used was made to 361 people in twelve private Colombian companies. An exploratory and Alpha factorial analysis of Cronbach was made, and through the difference of means common or distinctive patterns between companies were identified; and their influence on business sustainability. This descriptive study concludes that companies must understand and take on the new demands of the environment, their implications in the management and decision making, but also renew the knowledge to develop competencies that allow to fulfill the good government. It is also concluded that recognition by the environment and the sector is a key factor in companies, due to their high degree of compliance with the legal framework and confirmation of transparency in the management and decision making processes of the company. © 2018.